Peran Orang Tua dalam Menstimulasi Perkembangan Kognitif Anak Usia Dini - Anggria Novita (Institut Agama Islam Negeri Langsa, 2018)
This article was intended to reveal the importance of parental awareness in understanding children's growth and development. Parents is the first education place and the teacher is the second for early childhood. This descriptive qualitative research was conducted in a case study. Data were obtained by observation and interview with parents and teachers. The results of this study were (1) The role of parents in stimulating children's cognitive development was as: (observers, motivators, facilitators, education place, and problem solvers); (2) Impact of parents' role on children's cognitive development was the children were motivated to learn at home, became more critical and active, experienced improvement in achieving learning outcomes, were able to express their ideals and to bring up character of responsibility and confidence.